Financial Literacy and Fintech Exposure As Determinants of Investment Decisions: The Mediating Role of Investment Interests – A Study of Individual Investors in Hyderabad, India - Jaffer, Syed; Zaheeruddin , Mohamed; N, Roopalatha; Sultana , Farhana; Babu , GNPV; Kumar , Pinninti Siva (International Journal of Accounting and Economics Studies, 2025)
The evolution of the financial sector, particularly the rise of financial technologies (Fintech), ‎has reshaped how individual investors make investment decisions. This study investigates the ‎influence of financial literacy and fintech exposure on individual investment decisions in the ‎underexplored emerging markets like Hyderabad, emphasising the mediating role of ‎investment interest. Drawing on behavioural finance theory and empirical studies, the research ‎explores how informed financial understanding and engagement with digital financial ‎platforms shape investment behaviour. The data is collected using a structured survey method ‎from 311 individual investors in Hyderabad, India. For the study, Structural ‎Equation Modelling (SEM) was employed to test relationships among the constructs. Unlike ‎prior studies that have often examined financial literacy or fintech exposure in isolation, this ‎paper uniquely integrates these two determinants with the mediating mechanism of ‎investment interest, providing a comprehensive model of investment decision-making in the ‎Indian context.‎ The study contributes to the understanding of investment psychology within the Indian ‎context and offers insights for policy-makers and financial institutions aiming to foster ‎inclusive and informed investment ecosystems. It can be concluded that financial literacy ‎positively influences investment decisions by providing investors with the necessary ‎knowledge and skills to evaluate options critically and confidently‎.